2021
DOI: 10.3389/feduc.2021.575926
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Relative Importance of Student Motivation for Science and Mathematics Achievement in TIMSS

Abstract: Although motivation has been shown to have substantial influence on learning, the relative significance of Students’ motivational characteristics, compared to other school-related factors, for student learning and performance is still unclear. Furthermore, knowledge about the relative importance of different situational variables for predicting these motivational characteristics is crucial for educational decisions about how to enhance student motivation. This study examined (1) the relative importance of moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 88 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…To this end, a near-consensus exists in the literature that motivation plays crucial roles in students' achievement (Middleton & Spanias, 1999). This has informed a plethora of studies that have found justifications for explaining achievement differences based on variations in students' levels of motivation (Wilkins, 2004;Winberg & Palm, 2021).…”
Section: Theoretical Background Motivation and Students' Achievementmentioning
confidence: 99%
See 4 more Smart Citations
“…To this end, a near-consensus exists in the literature that motivation plays crucial roles in students' achievement (Middleton & Spanias, 1999). This has informed a plethora of studies that have found justifications for explaining achievement differences based on variations in students' levels of motivation (Wilkins, 2004;Winberg & Palm, 2021).…”
Section: Theoretical Background Motivation and Students' Achievementmentioning
confidence: 99%
“…In pursuit of this, Ersan and Rodriguez included malleable factors (e.g., interest) into their model even as they found that "SES at both student and school levels is a dominant factor related to mathematics achievement and a much stronger predictor at the school level" (2020, p. 1). Relatedly, Winberg and Palm's (2021) study of 300 variables that were hypothesized to account for achievement differences magnified the fundamental roles of students' self-concept, interest, and usefulness. Perhaps a consequence of their multicollinear nature, they found that these variables better function as a collective rather than isolated predictors of achievement.…”
Section: Achievement Within the Motivation Triadmentioning
confidence: 99%
See 3 more Smart Citations